INFLUENCE OF WORK POSTURE ON THE OCCURRENCE OF DISORDERS OF THE MUSCULOSKELETAL SYSTEM AMONG WORKERS IN THE TOBACCO INDUSTRY - Momčilović Vasilov, Jelena (Acta medicae Medianae, 2026)
Musculoskeletal system disordes (MSDs) require special attention because they represent one of the leading causes of absence from work and disability in the world. In addition to affecting the quality of life itself, they greatly reduce the ability to work, and can occur at any age. Their multi-factorial etiologies primarily caused by the interaction of an unhealthy lifestyle and workplace conditions that vary in different occupations. This research aimed to examine the prevalence of musculoskeletal system disorders among workers of the Niš Tobacco Industry (Niš TI), as well as the influence of the position of workers and other work-related factors on the occurrence of musculoskeletal disorders. Out of a total of 426 workers examined during the 2022 systematic examination, 69 (16.2%) workers were found to have musculoskeletal disorders. Musculoskeletal disorders were more prevalent in workers in the direct production sector (standing position), 61 (88.41%), in female workers (40.6%), and are also associated with overweight and old age of workers. The high frequency of musculoskeletal disorders among Niš TI employees indicates that it is necessary to take adequate prevention, control, and risk reduction measures for the occurrence of diseases and injuries of the musculoskeletal system, all with the aim of reducing the frequency of diseases, reducing the risk of disability, improving the quality of life, and increasing work ability.